Biological Impact of Transpulmonary Driving Pressure in Experimental Acute Respiratory Distress Syndrome. (August 2015) - Samary, Cynthia S.; Santos, Raquel S.; Santos, Cíntia L.; Felix, Nathane S.; Bentes, Maira; Barboza, Thiago; Capelozzi, Vera L.; Morales, Marcelo M.; Garcia, Cristiane S. N. B.; Souza, Sergio A. L.; Marini, John J.; Gama de Abreu, Marcelo; et al.
Abstract : Background: Ventilator-induced lung injury has been attributed to the interaction of several factors: tidal volume (VT ), positive end-expiratory pressure (PEEP), transpulmonary driving pressure (difference between transpulmonary pressure at end-inspiration and end-expiration, ΔP, L), and respiratory system plateau pressure (Pplat, rs). Methods: Forty-eight Wistar rats received Escherichia coli lipopolysaccharide intratracheally. After 24 h, animals were randomized into combinations of VT and PEEP, yielding three different ΔP, L levels: ΔP, LLOW (VT = 6 ml/kg, PEEP = 3 cm H2 O); ΔP, LMEAN (VT = 13 ml/kg, PEEP = 3 cm H2 O or VT = 6 ml/kg, PEEP = 9.5 cm H2 O); and ΔP, LHIGH (VT = 22 ml/kg, PEEP = 3 cm H2 O or VT = 6 ml/kg, PEEP = 11 cm H2 O). In other groups, at low VT, PEEP was adjusted to obtain a Pplat, rs similar to that achieved with ΔP, LMEAN and ΔP, LHIGH at high VT . Results: At ΔP, LLOW, expressions of interleukin (IL)-6, receptor for advanced glycation end products (RAGE), and amphiregulin were reduced, despite morphometric evidence of alveolar collapse. At ΔP, LHIGH (VT = 6 ml/kg and PEEP = 11 cm H2 O), lungs were fully open and IL-6 and RAGE were reduced compared with ΔP, LMEAN (27.4 ± 12.9 vs. 41.6 ± 14.1 and 0.6 ± 0.2 vs. 1.4 ± 0.3, respectively), despite increased hyperinflation and amphiregulin expression. At ΔP, LMEAN (VT = 6 ml/kg and PEEP = 9.5 cm H2 O), when PEEP was not high enough to keep lungs open, IL-6, RAGE, and amphiregulin expression increased compared with ΔP, LLOW (41.6 ± 14.1 vs. 9.0 ± 9.8, 1.4 ± 0.3 vs. 0.6 ± 0.2, and 6.7 ± 0.8 vs. 2.2 ± 1.0, respectively). At Pplat, rs similar to that achieved with ΔP, LMEAN and ΔP, LHIGH, higher VT and lower PEEP reduced IL-6 and RAGE expression. Conclusion: In the acute respiratory distress syndrome model used in this experiment, two strategies minimized ventilator-induced lung injury: (1) low VT and PEEP, yielding low ΔP, L and Pplat, rs; and (2) low VT associated with a PEEP level sufficient to keep the lungs open. Abstract : Different combinations of tidal volume and positive end-expiratory pressure (PEEP) were used to create a range of driving pressures in a rat model of acute respiratory distress syndrome due to tracheal instillation of endotoxin for 24 h. Low transpulmonary driving pressure was associated with alveolar collapse and high driving pressure was associated with hyperinflation. The combination of a tidal volume of 6 ml/kg predicted body weight and the lowest PEEP and driving pressure to maintain oxygenation in a normal range minimized ventilator-induced lung injury even in the presence of alveolar collapse.Supplemental Digital Content is available in the text.